Situation Report: Hungary, 18 April 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Private Enterprise in the Catering Industry: The Gebines Manager Restrictions on the Use of Cars in Enterprises Lack of Political Awareness among Party Workers Ten Years of Hungarian-East German Economic Co-Operation Lack of Student Hostels: A Serious Educational Problem Nepszabadsag on Student Protest Shortcomings in Work of House of Culture Lack of Irrigation Affects Seasonal Agricultural Work New Measures to Increase Vegetable Output